1980
DOI: 10.1002/1520-6807(198004)17:2<264::aid-pits2310170219>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perceptions of behavior problems in children from intact, single-parent, and stepparent families

Abstract: This study examined differences in the incidence of behavior problems between children living with both natural parents and those in single-parent or in stepparent families. Subjects were 3,644 white children in kindergarten through eighth grade; 2,991 were living with both of their own parents; 312 with mother only; 43 with father only; 264 with mother and stepfather; and 34 with father and stepmother. Teachers provided background information and Behavior Problem Checklist ratings on the youngsters. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Most studies suggested that high SES nontraditional families were more criminogenic; however, two classic studies by Touliatos and Lindholm (1980), and Goldstein (1984), as well as a more recent analysis by Hay, Forston, Hollist, Altheimer, and Schaible (2006), disputed these findings. Moreover, Kierkus and Baer (2003) found negligible evidence that the family structure/delinquency relationship varied according to SES.…”
Section: Ses Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies suggested that high SES nontraditional families were more criminogenic; however, two classic studies by Touliatos and Lindholm (1980), and Goldstein (1984), as well as a more recent analysis by Hay, Forston, Hollist, Altheimer, and Schaible (2006), disputed these findings. Moreover, Kierkus and Baer (2003) found negligible evidence that the family structure/delinquency relationship varied according to SES.…”
Section: Ses Interactionsmentioning
confidence: 99%
“…For instance, while some studies discovered that familial disruption was more stigmatizing in high SES settings, and consequently was more likely to be associated with antisocial behavior (Austin, 1978;Flewelling & Bauman, 1990;Johnstone, 1978;Rosen, 1985), others found that disruption was most criminogenic in low SES families because poor single parents were less able to provide the basic necessities of life for their children (Goldstein, 1984;Touliatos & Lindholm, 1980). Similarly, while certain authors (Austin, 1978;Bachman & Peralta, 2002;Wilkinson, 1980) reported that girls were more adversely affected by familial disruption than boys (because females were more "family oriented" than males), others (Canter, 1982;Dornbusch et al, 1985;Peterson & Zill, 1986;Schwartz, 2006) found that the process was more criminogenic for males.…”
Section: Introductionmentioning
confidence: 99%
“…Images of single-parent and stepparent families (Johnson, 1980;Lutz, 1980;Swihart & Brigham, 1982) and acceptance of single-parent and step parent families (Chng & Gray, 1983;Hetherington, 1981;Lombana, 1983;Touliatos & Lindholm, 1980 (Hetherington, 1979;Johnson, 1980, Lutz, 1980Swihart & Bingham, 1982). In some cases, this image is verifiable, but there are other cases in which it may be questionable.…”
Section: Development Of the Instrumentmentioning
confidence: 99%
“…With regard to acceptance of single-parent and stepparent families, research indicates that family forms are accepted more positively by family members (DiSibio, 1981;Furstenberg et al, 1983;Visher & Visher, 1979) than by their peers (Chng & Gray, 1983;Santrock, Warshak, & Meadows, 1981;Touliatos & Lindholm, 1980;Weiss, 1981). In addition, school personnel and society in general accept these family forms negatively (Drake & Shellenberger, 1980;Lombana, 1983;Swihart & Brigham, 1982).…”
Section: Development Of the Instrumentmentioning
confidence: 99%
See 1 more Smart Citation